BUSINESS DEVELOPMENT STRATEGY OF FISH MILLING (CASE STUDY OF ASIAH MILLING BUSINESS IN BENGKULU CITY) - Sintana, Alica; Trisusilo, Reswita, Agung; Rahayu, Heni Sulistyawati Purwaning (Jurnal Perikanan Unram, 2025)
Asiah Fish Milling Business, established in 2005, processes mackerel, snakehead fish, and parang-parang fish from the Pulau Baai Morning Market into quality groundfish. Although initially stable, this business faces challenges in growth and profits, especially because the marketing reach is limited in Bengkulu City. In addition, the availability of raw materials, price fluctuations, changes in market demand, competition, and shifts in consumption patterns also affect sales. This study aims to analyze the development strategy of Asiah's fish milling business in Bengkulu City. The research method uses SWOT and QSPM analysis. The study results are an aggressive strategy; this business has strengths that can be used to create profitable opportunities, with S-O (Strength-Opportunity) recommendations, namely increasing efficiency and quality with easily obtained supporting tools and optimizing capital for expansion and innovation. The use of efficient tools facilitates production and reduces waste, while capital management allows investment in technology and product development. Business expansion will increase production capacity and expand the market, supporting sustainable growth and business competitiveness.